Bonding method for low-glue-consumption high-strength plywood based on lignin formaldehyde-free adhesive

By pretreating ligno fiber raw materials with choline chloride, long-chain diol and maleic acid, a high-viscosity lignin-free adhesive was prepared. Combined with hot pressing curing technology, the problems of free formaldehyde release and low bonding strength of plywood were solved. The production of high-strength plywood is realized and suitable for industrialization.

CN119119879AActive Publication Date: 2024-12-13INST OF CHEM IND OF FOREST PROD CHINESE ACAD OF FORESTRY

Patent Information

Application Number
CN202411243122.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

Existing plywood adhesives have problems with free formaldehyde release, and lignin-free adhesives have low bond strength and no industrial utilization methods have been found, resulting in limited development.

Method used

The ligno fiber raw materials are pretreated by a mixed solution composed of choline chloride, long-chain diol and maleic acid to prepare high-viscosity lignin-free adhesive, and the bonding of high-strength plywood is achieved through hot pressing curing technology. , the amount of glue is lower than that of traditional adhesives, and the scope of application is wide.

Benefits of technology

The bonding of high-strength plywood is achieved, with dry strength reaching 0.9~1.3MPa and wet strength reaching 0.8~1.0MPa, exceeding the national standard, significantly improving the mechanical properties of plywood, reducing the amount of glue, and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119879A_ABST
    Figure CN119119879A_ABST
Patent Text Reader

Abstract

The invention discloses a bonding method for low-glue-consumption high-strength plywood based on a lignin formaldehyde-free adhesive, and belongs to the technical field of adhesives. The lignin-based formaldehyde-free adhesive is adopted to adhere the veneers, the single-face adhesive applying amount does not exceed 80 g / m < 2 >, and after hot-pressing curing, the bonding strength of the prepared high-strength plywood is not lower than 0.7 MPa; the lignin-based formaldehyde-free adhesive is prepared by separating and treating a wood fiber raw material or sulfate lignin with a mixed solution. After the adhesive disclosed by the invention is used for bonding three layers of poplar veneers, the dry strength can reach 0.9-1.3 MPa, and the class II wet strength can reach 0.8-1.0 MPa; the elasticity modulus and the static bending intensity of the plywood are obviously higher than 5500 MPa and 32 MPa after the plywood is bonded with five layers of plywood; the plywood manufactured by the method disclosed by the invention is far better than industrial urea-formaldehyde resin adhesive bonded plywood, and the bonding strength of the plywood is equivalent to that of industrial phenolic aldehyde bonded plywood.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and more specifically, relates to a bonding method for high-strength plywood with low glue application amount based on lignin formaldehyde-free adhesive. Background Art

[0002] The adhesives used in plywood are mainly phenolic, urea-formaldehyde, and melamine resins. These adhesives use formaldehyde as the main raw material, and there is a problem of free formaldehyde release. The development of formaldehyde-free adhesives can effectively solve the problem of free formaldehyde release and has broad market prospects. Lignin, as an adhesive in plant cells, gives the plant body rigidity and the ability to resist external erosion. Conventional lignin separation causes great damage to the structure of lignin. Most of the lignin obtained has a series of problems such as low purity, low activity, and large molecular weight distribution. It needs to be modified to meet the subsequent preparation requirements of adhesives. The low lignin yield, high cost, and high toxicity caused by the processes of lignin screening, purification, and modification have seriously restricted the development of lignin formaldehyde-free adhesives.

[0003] The inventors have previously discovered that a system composed of polyols, maleic acid, and choline chloride has a good pretreatment effect on wood fiber raw materials, can remove most of the lignin in the wood fiber raw materials, and the separated lignin is directly present as a flowable viscous adhesive, which can achieve bonding of different materials at room temperature (Chinese patent: CN115029104A A method for preparing a lignin formaldehyde-free adhesive and its product), but the bonding strength is relatively low, the bonding mechanism is unclear, and its industrial utilization path has not yet been found.

[0004] In order to solve the above problems, this application uses the lignin formaldehyde-free adhesive for the bonding of plywood and explains and optimizes its bonding mechanism and curing process, which is expected to open up a new market for the product for plywood bonding and completely solve the problem of free formaldehyde release from plywood. Summary of the invention

[0005] In view of the above problems existing in the prior art, the technical problem to be solved by the present invention is to provide a method for bonding high-strength plywood with low glue application amount based on lignin formaldehyde-free adhesive, which can achieve high-strength bonding of wood veneers.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0007] A method for bonding high-strength plywood with low glue application amount based on lignin-based formaldehyde-free adhesive, wherein the veneer is bonded with the lignin-based formaldehyde-free adhesive, and the glue application amount on one side is no more than 80g / m 2After hot pressing and curing, the bonding strength of the high-strength plywood is not less than 0.7MPa; the lignin-based formaldehyde-free adhesive is prepared by separating and treating wood fiber raw materials or sulfate lignin with a mixed solution; wherein the mixed solution is composed of choline chloride, long-chain diols and maleic acid.

[0008] Preferably, the single board is made of poplar.

[0009] Preferably, the hot pressing temperature is 150-190° C., the pressure is 1 MPa, and the hot pressing time is 1.1-4.4 min / mm.

[0010] The preparation process of the lignin formaldehyde-free adhesive is as follows:

[0011] 1) mixing choline chloride, long-chain diol and maleic acid in a molar ratio of 1:0.5-2:1-2, and heating at 90° C. until a uniform and transparent DES solution is formed;

[0012] 2) mixing the wood fiber raw material or kraft lignin with the DES solution obtained in step 1) at a mass ratio of 1:10, reacting at 100-140° C. for 6-12 hours, adding a solvent 3-5 times the volume of the mixed solution after the reaction, stirring and solid-liquid separation, rotary evaporating the obtained solution to remove the solvent, washing with water, and drying to obtain a lignin formaldehyde-free adhesive.

[0013] The bonding method of the low-sizing high-strength plywood based on the lignin formaldehyde-free adhesive specifically comprises the following steps:

[0014] 1) Preparation of lignin formaldehyde-free adhesive

[0015] Mix choline chloride, long-chain diol and maleic acid in a molar ratio of 1:0.5-2:1-2, and heat at 90° C. until a uniform and transparent DES solution is formed;

[0016] The lignocellulosic raw material or kraft lignin is mixed with the prepared DES solution in a mass ratio of 1:10, and reacted at 100-140° C. for 6-12 hours. After the reaction is completed, a solvent 3-5 times the volume of the mixed solution is added for stirring and solid-liquid separation, and the obtained solution is subjected to rotary evaporation to remove the solvent, and the lignin formaldehyde-free adhesive is obtained after washing with water and drying;

[0017] 2) Preparation of high-strength plywood

[0018] The lignin formaldehyde-free adhesive prepared in step 1) is directly and evenly applied on the surface of the veneer or evenly applied on the surface of the veneer after heating, and the amount of adhesive applied on one side is 50-75 g / m 2The fiber directions of adjacent veneers are perpendicular to each other, and the veneers are assembled and hot-pressed for curing. The hot-pressing temperature is 150-190°C, the pressure is 1.0MPa, and the hot-pressing time is 1.1-4.4min / mm to obtain high-strength plywood.

[0019] Preferably, the bonding method of the low-sizing high-strength plywood based on the lignin formaldehyde-free adhesive specifically comprises the following steps:

[0020] 1) Preparation of lignin formaldehyde-free adhesive

[0021] Choline chloride, 1,4-butanediol and maleic acid were mixed in a molar ratio of 1:2:1, heated at 90°C with constant stirring until a uniform, transparent DES solution was formed;

[0022] The kraft lignin and the prepared DES solution were mixed in a mass ratio of 1:10, and reacted at 110°C for 12 hours. After the reaction, hot water 3 times the volume of the mixed solution was added, and the mixture was stirred and then solid-liquid separated. The obtained lignin-rich pretreatment liquid was rotary evaporated, washed with water, and dried to obtain a lignin formaldehyde-free adhesive.

[0023] 2) Preparation of high-strength plywood

[0024] The lignin formaldehyde-free adhesive prepared in step 1) is evenly applied on the surface of the veneer, with a single-sided adhesive amount of 50 g / m 2 The fiber directions of adjacent veneers are perpendicular to each other to assemble the veneers to obtain a three-layer plywood blank, which is then hot-pressed and solidified at a temperature of 180°C, a pressure of 1.0 MPa, and a hot-pressing time of 2.2 min / mm to obtain a high-strength plywood.

[0025] Preferably, the bonding method of the low-sizing high-strength plywood based on the lignin formaldehyde-free adhesive specifically comprises the following steps:

[0026] 1) Preparation of lignin formaldehyde-free adhesive

[0027] Choline chloride, 1,4-butanediol and maleic acid were mixed in a molar ratio of 1:2:1, heated at 90°C with constant stirring until a uniform, transparent DES solution was formed;

[0028] The bamboo powder and the prepared DES solution were mixed in a mass ratio of 1:10, and reacted at 110°C for 6 hours. After the reaction, an ethanol aqueous solution with a volume of 5 times that of the mixed solution was added, and the mixture was stirred and then solid-liquid separated. The obtained lignin-rich pretreatment liquid was rotary evaporated, washed with water, and dried to obtain a lignin formaldehyde-free adhesive.

[0029] 2) Preparation of high-strength plywood

[0030] The lignin formaldehyde-free adhesive prepared in step 1) is evenly applied on the surface of the veneer, with a single-sided adhesive amount of 50 g / m 2 The fiber directions of adjacent veneers are perpendicular to each other to assemble the veneers to obtain a three-layer plywood blank, which is then hot-pressed and solidified at a temperature of 180°C, a pressure of 1.0 MPa, and a hot-pressing time of 2.2 min / mm to obtain a high-strength plywood.

[0031] Preferably, the bonding method of the low-sizing high-strength plywood based on the lignin formaldehyde-free adhesive specifically comprises the following steps:

[0032] 1) Preparation of lignin formaldehyde-free adhesive

[0033] Choline chloride, 1,4-butanediol and maleic acid were mixed in a molar ratio of 1:1:1, heated at 90°C with constant stirring until a uniform, transparent DES solution was formed;

[0034] The kraft lignin and the prepared DES solution were mixed in a mass ratio of 1:10, and reacted at 100°C for 12 hours. After the reaction, hot water 3 times the volume of the mixed solution was added, and the mixture was stirred to separate the solid and liquid. The obtained lignin-rich pretreatment liquid was rotary evaporated, washed with water, and dried to obtain a lignin formaldehyde-free adhesive.

[0035] 2) Preparation of high-strength plywood

[0036] The lignin formaldehyde-free adhesive prepared in step 1) is evenly applied on the surface of the veneer, with a single-sided adhesive amount of 50 g / m 2 The fiber directions of adjacent veneers are perpendicular to each other to assemble the veneers to obtain a three-layer plywood blank, which is then hot-pressed and solidified at a temperature of 180°C, a pressure of 1.0 MPa, and a hot-pressing time of 2.2 min / mm to obtain a high-strength plywood.

[0037] Preferably, the bonding method of the low-sizing high-strength plywood based on the lignin formaldehyde-free adhesive specifically comprises the following steps:

[0038] 1) Preparation of lignin formaldehyde-free adhesive

[0039] Choline chloride, 1,4-butanediol and maleic acid were mixed in a molar ratio of 1:1:1, heated at 90°C with constant stirring until a uniform, transparent DES solution was formed;

[0040] The bamboo powder and the prepared DES solution were mixed in a mass ratio of 1:10, and reacted at 100°C for 6 hours. After the reaction, an ethanol aqueous solution with a volume of 5 times that of the mixed solution was added, and the mixture was stirred for solid-liquid separation. The obtained lignin-rich pretreatment liquid was rotary evaporated, washed with water, and dried to obtain a lignin formaldehyde-free adhesive.

[0041] 2) Preparation of high-strength plywood

[0042] The lignin formaldehyde-free adhesive prepared in step 1) is evenly applied to the surface of the veneer, with a single-sided adhesive amount of 50 g / m 2 The fiber directions of adjacent veneers are perpendicular to each other to form veneers, and three-layer plywood is obtained. The veneers are then hot-pressed and solidified at a temperature of 180°C, a pressure of 1.0 MPa, and a hot-pressing time of 2.2 min / mm to obtain a high-strength plywood.

[0043] Preferably, the bonding method of the low-sizing high-strength plywood based on the lignin formaldehyde-free adhesive specifically comprises the following steps:

[0044] 1) Preparation of lignin formaldehyde-free adhesive

[0045] Choline chloride, 1,4-butanediol and maleic acid were mixed in a molar ratio of 1:1:1, heated at 90°C with constant stirring until a uniform, transparent DES solution was formed;

[0046] The kraft lignin and the prepared DES solution were mixed in a mass ratio of 1:10, and reacted at 110°C for 12 hours. After the reaction, hot water 3 times the volume of the mixed solution was added thereto, and the mixture was stirred and then solid-liquid separated. The obtained lignin-rich pretreatment liquid was rotary evaporated, washed with water, and dried to obtain a lignin formaldehyde-free adhesive.

[0047] 2) Preparation of high-strength plywood

[0048] The lignin formaldehyde-free adhesive prepared in step 1) is evenly applied to the surface of the veneer, with a single-sided adhesive amount of 50g / m 2 The fiber directions of adjacent veneers are perpendicular to each other to form veneers, and three-layer plywood is obtained. The veneers are then hot-pressed and solidified at a temperature of 180°C, a pressure of 1.0 MPa, and a hot-pressing time of 2.2 min / mm to obtain a high-strength plywood.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] 1) The lignin formaldehyde-free adhesive used in the present invention is a brown fluid with a certain viscosity. The viscosity of the adhesive is 109-10709 Pa·s at room temperature. As the temperature rises from room temperature to 100°C, the viscosity of the adhesive can be significantly reduced to 0.2-11 Pa·s, indicating that the adhesive can meet the gluing requirements under different conditions by simple temperature control;

[0051] 2) The present invention can achieve high-strength bonding of wood veneers. The dry strength of three-layer poplar veneers after bonding can reach 0.9-1.3MPa, and the Class II wet strength can reach 0.8-1.0MPa, meeting the national standard requirement of 0.7MPa (GB / T9846-2015); the elastic modulus and static bending strength of five-layer plywood after bonding are 9375-9678MPa and 74-91MPa, respectively, which are significantly higher than the national standard requirements of 5500MPa and 32MPa, far exceeding the industrial urea-formaldehyde resin glue-bonded plywood, and the bonding strength is equivalent to that of industrial-grade phenolic resin glue-bonded plywood;

[0052] 3) The lignin-based formaldehyde-free adhesive prepared by the present invention has a sizing amount of only 50 g / m 2 For bonding wood boards, the amount of glue applied is significantly lower than that of traditional phenolic and urea-formaldehyde adhesives. The hot pressing temperature, time and pressure range are wide, and it can be applied to most woods and hot pressing equipment, and has good industrial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 Graphs showing the lignin removal rate and adhesive recovery rate of the lignin formaldehyde-free adhesives prepared in Examples 1-13; wherein, Graph a shows the lignin removal rate and adhesive recovery rate of the lignin formaldehyde-free adhesives prepared in Examples 1-4; Graph b shows the lignin removal rate and adhesive recovery rate of the lignin formaldehyde-free adhesives prepared in Examples 3, 5-7; Graph c shows the lignin removal rate and adhesive recovery rate of the lignin formaldehyde-free adhesives prepared in Examples 3, 8-11; Graph d shows the lignin removal rate and adhesive recovery rate of the lignin formaldehyde-free adhesives prepared in Examples 3, 12-13;

[0054] Figure 2 The bonding strength diagram of the lignin formaldehyde-free adhesive prepared in Example 3 for bonding three-layer plywood under different hot pressing conditions and glue application amounts; Figure a shows the bonding strength of the three-layer plywood when the glue application amount is 50g / m 2 Figure a is the bonding strength diagram under different hot pressing conditions, and Figure b is the bonding strength diagram under different glue application amounts when the hot pressing temperature and time are 180℃ and 10min respectively;

[0055] Figure 3 The bonding strength diagrams of three-layer plywood bonded by enzymatically hydrolyzed ground wood lignin (CEL) without DES solvent treatment are shown in FIG. 1-13; FIG. a is a bonding strength diagram of three-layer plywood bonded by lignin formaldehyde-free adhesive prepared by Example 1-4; FIG. b is a bonding strength diagram of three-layer plywood bonded by lignin formaldehyde-free adhesive prepared by Example 3, 8-11; FIG. c is a bonding strength diagram of three-layer plywood bonded by lignin formaldehyde-free adhesive prepared by Example 3, 5-7; FIG. d is a bonding strength diagram of three-layer plywood bonded by lignin formaldehyde-free adhesive prepared by Example 3, 12-13;

[0056] Figure 4 The viscosity diagram of the lignin formaldehyde-free adhesive prepared in Examples 3 and 5-11;

[0057] Figure 5 The elastic modulus and static bending strength diagram of five-layer plywood bonded with phenolic resin and urea-formaldehyde resin in Examples 3, 7, 10;

[0058] Figure 6 The two-dimensional NMR characterization results of the lignin formaldehyde-free adhesive prepared in Examples 3, 5, and 7 and the enzymatically hydrolyzed milled wood lignin (CEL) not treated with DES solvent; wherein, Figure a is the fat region of the two-dimensional NMR spectrum, and Figure b is the aromatic region of the two-dimensional NMR spectrum;

[0059] Figure 7 The infrared spectra of the lignin formaldehyde-free adhesive, poplar veneer, and plywood bonding surface after hot pressing prepared in Example 3;

[0060] Figure 8 It is a graph of adhesive recovery rates of the lignin formaldehyde-free adhesives prepared in Examples 19-26; wherein, Figure a is a graph of adhesive recovery rates of the lignin formaldehyde-free adhesives prepared in Examples 19-22, and Figure b is a graph of adhesive recovery rates of the lignin formaldehyde-free adhesives prepared in Examples 19 and 23-26;

[0061] Fig. 9 This is a bonding strength diagram of the poplar three-layer board bonded with the lignin formaldehyde-free adhesive prepared in Examples 19-26; wherein, Figure a is a bonding strength diagram of the poplar three-layer board bonded with the lignin formaldehyde-free adhesive prepared in Examples 19-22, and Figure b is a bonding strength diagram of the poplar three-layer board bonded with the lignin formaldehyde-free adhesive prepared in Examples 19 and 23-26. DETAILED DESCRIPTION

[0062] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described below in conjunction with specific embodiments. In the following examples, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0063] Example 1

[0064] A method for preparing a lignin formaldehyde-free adhesive comprises the following steps:

[0065] 1) choline chloride, 1,2-pentanediol and maleic acid were mixed in a molar ratio of 1:1:1, heated at 90°C with constant stirring until a uniform and transparent DES solution was formed;

[0066] 2) mixing the bamboo powder with the DES solution obtained in step 1) at a mass ratio of 1:10, reacting at 110° C. for 6 h, adding 5 times the volume of the mixed solution of ethanol aqueous solution after the reaction, wherein the volume concentration of the ethanol aqueous solution is 50%, stirring for 1 h, and separating the solid and liquid to obtain a lignin-rich pretreatment liquid and a pretreatment material;

[0067] 3) The lignin-rich pretreatment liquid was subjected to rotary evaporation at 70° C. to remove ethanol therein, and appropriate deionized water was added to precipitate the lignin, the supernatant was discarded, deionized water was added to stir and wash, and the mixture was dried in an oven at 70° C. to obtain a lignin formaldehyde-free adhesive.

[0068] Example 2

[0069] When preparing the lignin formaldehyde-free adhesive, choline chloride, 1,2-butanediol and maleic acid are mixed in a molar ratio of 1:1:1, and the remaining preparation methods and parameters are the same as those in Example 1.

[0070] Example 3

[0071] When preparing the lignin formaldehyde-free adhesive, choline chloride, 1,4-butanediol and maleic acid were mixed in a molar ratio of 1:1:1, and the remaining preparation methods and parameters were the same as those in Example 1.

[0072] Example 4

[0073] When preparing the lignin formaldehyde-free adhesive, choline chloride, 1,5-pentanediol and maleic acid are mixed in a molar ratio of 1:1:1, and the remaining preparation methods and parameters are the same as those in Example 1.

[0074] The pretreated materials obtained in Examples 1-4 were neutralized with distilled water, and the main component content was analyzed, and the lignin removal rate was calculated; the lignin formaldehyde-free adhesive dried in an oven at 70°C was weighed to calculate the yield, and the yield was calculated based on the mass of lignin added to the reaction system. The results are shown in FIG. Figure 1 a and Table 1.

[0075] Table 1 Lignin removal rate and adhesive recovery rate of lignin-based adhesives prepared in Examples 1-4

[0076] Example 1 Example 2 Example 3 Example 4 Lignin removal rate (%) 62.7 71.1 78.8 81.0 Adhesive recovery rate (%) 315.4 389.5 426.7 521.5

[0077] Depend on Figure 1 a and Table 1 show that the lignin removal rate of the bamboo raw material treated with different choline chloride / polyol / maleic acid systems is 61.6% to 81.0%, indicating that DES with different polyol groups have different dissociation effects on the wood fiber raw material; the lignin obtained after pretreatment with DES with different long-chain polyol groups is a fluid adhesive with a certain viscosity, and the yield is 315.4% to 521.5%.

[0078] Example 5

[0079] When preparing the lignin formaldehyde-free adhesive, choline chloride, 1,4-butanediol and maleic acid are mixed in a molar ratio of 1:2:1, and the remaining preparation methods and parameters are the same as those in Example 3.

[0080] Example 6

[0081] When preparing the lignin formaldehyde-free adhesive, choline chloride, 1,4-butanediol and maleic acid were mixed in a molar ratio of 1:0.5:1, and the remaining preparation methods and parameters were the same as those in Example 3.

[0082] Example 7

[0083] When preparing the lignin formaldehyde-free adhesive, choline chloride, 1,4-butanediol and maleic acid were mixed in a molar ratio of 1:1:2, and the remaining preparation methods and parameters were the same as those in Example 3.

[0084] The pretreated materials obtained in Example 3 and Examples 5-7 were neutralized with distilled water, and the main component content was analyzed and the lignin removal rate was calculated; the lignin formaldehyde-free adhesive dried in an oven at 70°C was weighed and the yield was calculated based on the mass of lignin added to the reaction system. The results are shown in FIG. Figure 1 b and Table 2.

[0085] Table 2 Lignin removal rate and adhesive recovery rate of lignin formaldehyde-free adhesives prepared in Examples 3, 5-7

[0086] Example 3 Example 5 Example 6 Example 7 Lignin removal rate (%) 78.8 76.9 78.9 76.1 Adhesive recovery rate (%) 426.7 252.8 426.7 801.4

[0087] Depend on Figure 1 b and Table 2 show that after pretreatment with different molar ratios of choline chloride / 1,4-butanediol / maleic acid, the lignin removal rate does not change much (76.1% to 78.9%), indicating that the dissociation efficiency of wood fiber raw materials under different molar ratios of this system is similar. However, the recovery rate of lignin formaldehyde-free adhesive varies greatly, and it increases significantly with the increase of maleic acid dosage (252.8% to 801.4%), indicating that the increase of maleic acid dosage can significantly promote the cross-linking reaction of lignin with DES solvent in this pretreatment system. The esterification reaction of maleic acid and 1,4-butanediol and the grafting cross-linking reaction with lignin side chains are important reaction processes for the formation of lignin formaldehyde-free adhesive.

[0088] Example 8

[0089] When preparing the lignin formaldehyde-free adhesive, the bamboo powder was mixed with the DES solution prepared in step 1) at a mass ratio of 1:10 and reacted at 100° C. for 6 h. The remaining preparation methods and parameters were the same as those in Example 3.

[0090] Example 9

[0091] When preparing the lignin formaldehyde-free adhesive, the bamboo powder was mixed with the DES solution prepared in step 1) at a mass ratio of 1:10 and reacted at 120° C. for 6 h. The remaining preparation methods and parameters were the same as those in Example 3.

[0092] Example 10

[0093] When preparing the lignin formaldehyde-free adhesive, the bamboo powder was mixed with the DES solution prepared in step 1) at a mass ratio of 1:10 and reacted at 130° C. for 6 h. The remaining preparation methods and parameters were the same as those in Example 3.

[0094] Embodiment 11

[0095] When preparing the lignin formaldehyde-free adhesive, the bamboo powder was mixed with the DES solution prepared in step 1) at a mass ratio of 1:10 and reacted at 140° C. for 6 h. The remaining preparation methods and parameters were the same as those in Example 3.

[0096] The pretreated materials obtained in Example 3 and Examples 8-11 were neutralized with distilled water, and the main component content was analyzed and the lignin removal rate was calculated; the lignin formaldehyde-free adhesive dried in an oven at 70°C was weighed and the yield was calculated based on the mass of lignin added to the reaction system. The results are shown in FIG. Figure 1 c and Table 3.

[0097] Table 3 Lignin removal rate and adhesive recovery rate of lignin formaldehyde-free adhesives prepared in Examples 3, 8-11

[0098] Example 3 Example 8 Example 9 Example 10 Embodiment 11 Lignin removal rate (%) 78.8 72.0 85.0 82.4 74.5 Adhesive recovery rate (%) 426.7 237.8 589.7 667.2 942.1

[0099] Depend on Figure 1 c and Table 3 show that the lignin removal rate gradually increases from 72.0% (100℃) to 85.0% (120℃) with the increase of temperature. As the temperature continues to rise, the lignin polycondensation reaction intensifies and the lignin removal rate decreases. At the same time, the recovery rate of lignin formaldehyde-free adhesive increases significantly from 237.8% to 942.1%, indicating that increasing the temperature can significantly increase the esterification cross-linking reaction of lignin with DES solvent. However, the increase in the cross-linking reaction between the solvent and lignin will form a greater steric hindrance, which in turn affects the reaction of the active sites on the lignin benzene ring with the components in the wood fiber raw material.

[0100] Example 12

[0101] When preparing the lignin formaldehyde-free adhesive, poplar wood is selected as the wood fiber raw material, and the remaining preparation methods and parameters are the same as those in Example 3.

[0102] Example 13

[0103] When preparing the lignin formaldehyde-free adhesive, Masson pine was selected as the wood fiber raw material, and the remaining preparation methods and parameters were the same as those in Example 3.

[0104] The pretreated materials obtained in Examples 3 and 12-13 were neutralized with distilled water, and the main component content was analyzed, and the lignin removal rate was calculated; the lignin formaldehyde-free adhesive dried in an oven at 70°C was weighed to calculate the yield, and the yield was calculated based on the mass of lignin added to the reaction system. The results are shown in FIG. Figure 1 d and shown in Table 4.

[0105] Table 4 Lignin removal rate and adhesive recovery rate of lignin formaldehyde-free adhesives prepared in Examples 3, 12-13

[0106] Example 3 Example 12 Example 13 Lignin yield (%) 78.8 70.4 48.5 Adhesive recovery rate (%) 426.7 769.5 960.3

[0107] Depend on Figure 1 d and Table 4 show that when the molar ratio of choline chloride / 1,4-butanediol / maleic acid is 1:1:1 and 110℃ treatment for 6h is used as the optimal conditions for pretreatment of different wood fiber raw materials, the lignin removal rate after pretreatment of wood by this system is lower than that of bamboo of the Poaceae family, and the lignin removal rate of Masson pine is only 48.5%. This result is due to the relatively high degree of lignification of wood and the denser structure. The recovery rate of lignin glue (relative to the lignin removed in the system) is opposite to the lignin removal rate. The recovery rate of lignin formaldehyde-free adhesive after pretreatment of poplar and Masson pine is significantly higher than that of bamboo. This result shows that the structure of lignin in wood is more susceptible to cross-linking reaction with DES solvent.

[0108] Embodiment 14

[0109] A method for bonding high-strength plywood with low glue application amount based on lignin formaldehyde-free adhesive, comprising the following steps:

[0110] 1) The lignin formaldehyde-free adhesive prepared in Example 3 was used to bond three layers of plywood. The plywood was made of poplar veneer with a thickness of 1.5 mm. The poplar veneer was cut into lengths and widths of 140 mm and 120 mm, respectively.

[0111] 2) The amount of glue applied on one side is 50-100g / m 2 , the lignin glue is evenly applied to the surface of the poplar board by measuring and weighing.

[0112] 3) The fibers of adjacent layers of poplar veneers are placed perpendicular to each other and then cured by hot pressing in a hot press. The hot pressing temperature is 150-190° C., the pressure is 1.0 MPa, and the hot pressing time is 1.1-4.4 min / mm.

[0113] The molded plywood was cut into standard test pieces and then tested for dry strength and Class II wet strength using a universal tensile testing machine (SUNS UTM6503). Figure 2 shown.

[0114] Depend on Figure 2 It can be seen from a that when the glue application amount is 50g / m 2 When the hot pressing temperature is a relatively low 170°C, the required hot pressing time is 20 minutes, and the hot pressing time is significantly reduced to 10 minutes as the temperature increases (180-190°C). However, too high a hot pressing temperature is still difficult to meet the actual industrial production. The present invention can significantly reduce the hot pressing temperature to 150°C / 10 minutes by introducing a small amount of sulfuric acid as a catalyst (0.1wt%) into the lignin adhesive obtained in Example 3. Under this condition, the dry and wet bonding strengths are 1.0 and 0.8MPa, both exceeding the minimum bonding strength of 0.7MPa required by the national standard.

[0115] Depend on Figure 2 b It can be seen that when the hot pressing temperature and time are 180°C and 10 min respectively, the present invention selects single-sided 50, 75, 100 g / m 2 The glue application amount was used for bonding, and it was found that 50g / m 2 The bonding strength of plywood can exceed the national standard requirements with the glue application amount from 50g / m 2 Increased to 75g / m 2 The dry and wet bonding strength of plywood increased from 1.2 / 1.0MPa to 1.4 / 1.1MPa, and the glue application amount continued to increase to 100g / m 2 , the strength of plywood almost stops increasing, indicating that 50-75g / m 2 The amount of glue applied is sufficient to meet the bonding strength requirements of the plywood. In summary, the amount of glue applied by the lignin formaldehyde-free adhesive is only 50g / m 2 , much lower than traditional phenolic and urea-formaldehyde wood adhesives (150-300g / m 2 ); The lignin formaldehyde-free adhesive has a wide range of hot pressing curing conditions, which can meet the needs of different plywood production equipment and has great potential for industrial production.

[0116] Embodiment 15

[0117] The three-layer plywood was bonded by using the enzymatically hydrolyzed groundwood lignin (CEL) of Examples 1-13 and the CEL that was not treated with DES solvent. The specific bonding process was as follows: the plywood was made of poplar veneer with a thickness of 1.5 mm and a single-sided glue amount of 50 g / m 2The fiber directions of adjacent layers of veneer are perpendicular to each other and then hot-pressed and cured. The hot-pressing temperature is 180℃, the pressure is 1.0MPa, and the hot-pressing time is 2.2min / mm. The formed plywood is cut into standard test pieces and then tested for dry strength and Class II wet strength using a universal tensile testing machine (SUNS UTM6503). The results are as follows Figure 3 As shown in Table 5.

[0118] Table 5 Bonding strength of three-layer plywood bonded with enzymatically degraded groundwood lignin (CEL) of Examples 1-13 and without DES solvent treatment

[0119]

[0120]

[0121] Depend on Figure 3 It can be seen from a that the dry and wet bonding strengths of the lignin formaldehyde-free adhesives prepared by DES pretreatment with different polyol groups for poplar plywood are both higher than 0.7 MPa, indicating that the adhesives prepared by this system can be used for the preparation of plywood.

[0122] Depend on Figure 3 b It can be seen that the dry strength and wet strength of the plywood bonded with enzymatically hydrolyzed ground wood lignin (CEL) without DES solvent treatment are 1.01 and 0.77 MPa, respectively, reaching the minimum requirement of 0.7 MPa of the national standard. However, the lignin is in powder form and is difficult to match with the current plywood gluing process, and the preparation process of CEL is complicated, costly, and has a low yield, making it difficult to achieve large-scale production. After pretreatment with DES solvent, lignin is in a viscous fluid state and can be heat-cured, which is very similar to the phenolic resin used in the plywood industry. The mechanical properties of the three-layer board bonded with lignin formaldehyde-free adhesive prepared under different conditions in this system are mostly better than those of the CEL bonded samples, indicating that the DES solvent can effectively activate lignin and increase its bonding opportunity with the main components of the wood fiber raw materials during the hot pressing process, thereby improving the bonding strength.

[0123] Depend on Figure 3 c shows that as the temperature in the DES solvent system increases ( Figure 3 b) and the increase in the use of maleic acid ( Figure 3 c), the dry and wet bonding strengths of plywood decreased from 1.32 and 1.03 MPa to 0.94 and 0.78 MPa, and from 1.46 and 0.80 MPa to 1.08 and 0.73 MPa, respectively, but still met the national standard requirements. The decrease in bonding strength is due to the increase in polycondensation reaction of lignin under the pretreatment conditions of strong acidity and high temperature, and the excessive cross-linking reaction between DES solvent and lignin, which increases the steric hindrance on the benzene ring of lignin, reducing the bonding opportunities between the adhesive and the components in the wood fiber raw material during the hot pressing process.

[0124] Depend on Figure 3 It can be seen from the data that the lignin formaldehyde-free adhesives obtained after pretreatment of three different raw materials of bamboo, poplar and Masson pine have similar bonding performance for poplar three-layer plywood, with dry strength and wet strength of 1.02-1.15MPa and 0.83-0.96MPa respectively, both exceeding the national standard of 0.7MPa bonding standard, indicating that this system can use a variety of different wood fiber raw materials to prepare lignin formaldehyde-free adhesives with high bonding performance.

[0125] Depend on Figure 4 It can be seen that the lignin formaldehyde-free adhesives (Examples 3, 5-11) obtained under different pretreatment conditions have a viscosity of 109-10709 Pa·s at room temperature, and the viscosity of the adhesive can be significantly reduced to 0.2-11 Pa·s as the temperature rises from room temperature to 100°C, indicating that the lignin formaldehyde-free adhesive can meet the sizing requirements under different conditions by simple temperature control. Specific viscosity data are shown in Table 6 below.

[0126] Table 6 Viscosity of lignin formaldehyde-free adhesives prepared in Examples 3, 5-11 at different temperatures

[0127]

[0128] Example 16

[0129] The five-layer plywood was bonded using Example 3, Example 7, Example 10, phenolic resin adhesive and urea-formaldehyde resin adhesive. The specific bonding process is as follows:

[0130] 1) The prepared lignin formaldehyde-free adhesive is used to bond five-layer plywood, the plywood is made of poplar veneer with a thickness of 1.5 mm, and the poplar veneer is cut into lengths and widths of 200 and 50 mm respectively;

[0131] 2) The amount of lignin formaldehyde-free adhesive applied on one side is 50g / m 2 The single-sided sizing amount of phenolic and urea-formaldehyde adhesive is 100g / m 2 , lignin glue is evenly applied to the surface of the poplar wood board by measuring and weighing;

[0132] 3) The fibers of adjacent layers of poplar veneers are placed perpendicular to each other and then cured by hot pressing in a hot press. The hot pressing temperature is 180° C., the pressure is 1.0 MPa, and the hot pressing time is 2.7 min / mm.

[0133] The elastic modulus and static bending strength of plywood were measured by an electronic universal tensile testing machine (SUNS UTM304SLXY, Shenzhen Sansi Zongheng Technology Co., Ltd.). Figure 5 And as shown in Table 7.

[0134] Table 7 Elastic modulus and static bending strength of five-layer plywood bonded with phenolic resin and urea-formaldehyde resin in Examples 3, 7, 10

[0135] Elastic modulus MPa Static bending strength MPa Example 3 9375.3 91.3 Example 7 9678.7 87.7 Example 10 9417.7 73.8 Phenolic resin adhesive 8943.0 88.2 Urea-formaldehyde resin adhesive 8151.3 69.7

[0136] Depend on Figure 5 As shown in Table 7, the elastic modulus and static bending strength of the adhesives prepared under different conditions are 9375-9679 MPa and 73.8-91.3 MPa, respectively. The static bending strength decreases significantly with the increase of maleic acid dosage and the increase of pretreatment temperature. This result is similar to the trend of the bonding strength of three-layer plywood. The high maleic acid dosage and the increase of lignin polycondensation reaction at the reaction temperature lead to excessive cross-linking reaction of lignin adhesive, resulting in a decrease in the active sites of lignin benzene rings and side chains, an increase in steric hindrance, and limiting the reaction of lignin adhesive with lignin and other components in the poplar board, resulting in a decrease in the bonding effect. However, the elastic modulus and static bending strength of the lignin adhesive prepared under the above different conditions are significantly higher than those of urea-formaldehyde resin adhesive, and higher than or close to phenol-formaldehyde resin. The results show that the performance of the adhesive prepared by this system in bonding multilayer boards is close to or better than that of traditional industrial-grade phenol-formaldehyde or urea-formaldehyde adhesives, and can replace fossil-based phenol-formaldehyde and urea-formaldehyde adhesives, becoming an emerging green bio-based formaldehyde-free plywood adhesive.

[0137] Embodiment 17

[0138] The lignin formaldehyde-free adhesives prepared in Examples 3, 5, and 7 and the enzymatically hydrolyzed ground wood lignin (CEL) not treated with DES solvent were dissolved in deuterated dimethyl sulfoxide and then characterized by two-dimensional nuclear magnetic resonance. Figure 6 and as shown in Table 8.

[0139] Table 8 Two-dimensional NMR characterization results of lignin formaldehyde-free adhesives prepared in Examples 3, 5, and 7 and enzymatically hydrolyzed milled wood lignin (CEL) not treated with DES solvent

[0140]

[0141] like Figure 6As shown in a, the CEL lignin fat region contains abundant β-O-4 aromatic ether bonds, β-β, and β-5 derivative peaks, with contents of 59 / 100Ar, 4 / 100Ar, and 5 / 100Ar, respectively. After pretreatment with choline chloride / 1,4-butanediol / maleic acid system at different molar ratios, the aromatic ether bonds decreased significantly to 9 / 100Ar (L121), 5 / 100Ar (L111), and 0 / 100Ar (L112). A new derivative peak A”α appears at 80.05 / 4.49ppm, which is considered to be the peak of butanediol or its derivatives connected to the α-position of the lignin side chain. In addition, the peak of oxidation at the γ-position of the lignin side chain in CEL is smaller (A'γ, 63.0 / 4.36ppm), while this peak (green circle) is significantly enhanced in the prepared adhesive. The enhancement of this peak is due to the esterification and cross-linking reaction between maleic acid and its derivatives and the γ-position hydroxyl group of the lignin side chain. With the increase of pretreatment intensity (increase in the amount of maleic acid), the butanediol or its derivatives connected to the α-position of the lignin side chain decreased significantly, and the content of aromatic ether bonds decreased from 55 / 100Ar (L121) to 53 / 100Ar (L111) and 0 (L112). This result is consistent with its bonding effect, indicating that the departure of the α-position group of the lignin side chain and the breaking of the aromatic ether bond will reduce the esterification and cross-linking of the adhesive with the cellulose and hemicellulose in the poplar veneer during the hot pressing process, thereby weakening the bonding strength.

[0142] The spectrum of lignin aromatic region is as follows Figure 6 As shown in Figure b, the main components of CEL lignin S, G, H and lignin carbohydrate related peaks (PCE) are clearly visible. After pretreatment, lignin undergoes polycondensation to varying degrees, and with the increase in the amount of maleic acid, the polycondensation reaction gradually increases from 4 / 100Ar (L121) to 10 / 100Ar (L111) and 28 / 100Ar (L112). The increase in polycondensation is consistent with the decrease in the bonding strength of plywood. Different from the CEL spectrum, the appearance of new derivative peaks at δC / δH129.0 / 6.2 and 132.9 / 6.7ppm is due to the esterification reaction of maleic acid or its derivatives with the γ position of the lignin side chain, which effectively extends the length of the lignin side chain and increases the carboxyl content of the lignin side chain.

[0143] Embodiment 18

[0144] The formation of the connecting bonds before and after bonding of the lignin formaldehyde-free adhesive prepared in Example 3 was characterized by infrared spectroscopy. The results are as follows: Figure 7 The bonding and curing process is as follows:

[0145] 1) The lignin formaldehyde-free adhesive prepared in Example 3 was used to bond three layers of plywood, the plywood was made of poplar veneer with a thickness of 1.5 mm, and the poplar veneer was cut into lengths and widths of 140 mm and 120 mm, respectively;

[0146] 2) The glue amount on one side is 50g / m 2 , lignin glue is evenly applied to the surface of the poplar wood board by measuring and weighing;

[0147] 3) The fibers of adjacent layers of poplar veneers are placed perpendicular to each other and then heat-pressed and cured in a hot press. The hot pressing temperature is 180°C, the pressure is 1.0 MPa, and the hot pressing time is 2.2 min / mm;

[0148] As shown in Figure 7, the carbonyl absorption peak of poplar veneer representing hemicellulose is located at 1730 cm -1 The relevant absorption peaks of lignin aromatic ring are located at 1602 and 1510 cm -1 Compared with poplar veneer, the carbonyl absorption peak in the prepared lignin formaldehyde-free adhesive was blue-shifted (1730-1713cm -1 ), indicating that the lignin formaldehyde-free adhesive contains more ester groups, which is consistent with the esterification reaction between maleic acid and its derivatives and the γ position of the lignin side chain in the NMR spectrum.

[0149] Lignin aromatic ring absorption peak (1602cm -1 and 1510cm -1 ) was significantly enhanced, indicating that the adhesive retained the aromatic ring skeleton structure of lignin. After the adhesive was hot-pressed with the poplar veneer, the surface of the plywood bonding surface contained abundant ester groups (1713cm -1 ) and the aromatic ring structure of lignin (1602cm -1 and 1510cm -1 ), indicating that a large amount of esterification cross-linking occurred between the adhesive and the poplar veneer, and the cross-linking reaction gave the plywood the bonding strength.

[0150] The grafting reaction of lignin side chains with butanediol, maleic acid and its derivatives is the main reason why lignin formaldehyde-free adhesives are in a viscous fluid state. During the hot pressing curing process of the adhesive, the esterification cross-linking of cellulose, hemicellulose and lignin in the wood board provides part of the structural strength of the plywood, and the more stable CC bonds formed by the polycondensation reaction of less polycondensed lignin with uncondensed lignin in the wood board provide another part of the structural strength of the plywood.

[0151] Embodiment 19

[0152] A method for preparing a lignin formaldehyde-free adhesive comprises the following steps:

[0153] 1) choline chloride, 1,4-butanediol and maleic acid were mixed in a molar ratio of 1:1:1, heated at 90°C with constant stirring until a uniform and transparent DES solution was formed;

[0154] 2) mixing the kraft lignin with the DES solution obtained in step 1) at a mass ratio of 1:10, reacting at 110° C. for 12 h. After the reaction, adding hot water (95° C.) 3 times the volume of the mixed solution, stirring for 1 h, and naturally settling for 5 h.

[0155] 3) After the liquid is separated into layers, the upper layer of liquid rich in DES solvent is poured out and rotary evaporated at 70°C to recover the DES solvent that has not participated in the reaction. The lignin adhesive precipitated in the lower layer is stirred and washed with deionized water until the washing liquid is neutral, and then dried in an oven at 70°C to obtain a lignin formaldehyde-free adhesive and calculate the yield, which is based on the mass of the added lignin.

[0156] Embodiment 20

[0157] When preparing the lignin formaldehyde-free adhesive, choline chloride, 1,4-butanediol and maleic acid are mixed in a molar ratio of 1:2:1, and the remaining preparation methods and parameters are the same as those in Example 19.

[0158] Embodiment 21

[0159] When preparing the lignin formaldehyde-free adhesive, choline chloride, 1,4-butanediol and maleic acid are mixed in a molar ratio of 1:1:2, and the remaining preparation methods and parameters are the same as those in Example 19.

[0160] Embodiment 22

[0161] When preparing the lignin formaldehyde-free adhesive, choline chloride, 1,4-butanediol and maleic acid are mixed in a molar ratio of 1:0.5:1, and the remaining preparation methods and parameters are the same as those in Example 19.

[0162] Embodiment 23

[0163] When preparing the lignin formaldehyde-free adhesive, the kraft lignin and the DES solution obtained in step 1) are mixed in a mass ratio of 1:10 and reacted at 100° C. for 12 h. The remaining preparation methods and parameters are the same as those in Example 19.

[0164] Embodiment 24

[0165] When preparing the lignin formaldehyde-free adhesive, the kraft lignin and the DES solution obtained in step 1) are mixed in a mass ratio of 1:10 and reacted at 120° C. for 12 h. The remaining preparation methods and parameters are the same as those in Example 19.

[0166] Embodiment 25

[0167] When preparing the lignin formaldehyde-free adhesive, the kraft lignin and the DES solution obtained in step 1) are mixed in a mass ratio of 1:10 and reacted at 130° C. for 12 h. The remaining preparation methods and parameters are the same as those in Example 19.

[0168] Embodiment 26

[0169] When preparing the lignin formaldehyde-free adhesive, the kraft lignin and the DES solution obtained in step 1) are mixed in a mass ratio of 1:10 and reacted at 140° C. for 12 h. The remaining preparation methods and parameters are the same as those in Example 19.

[0170] The pretreated materials obtained in Examples 19-26 were neutralized with distilled water, dried in an oven at 70°C, and weighed to calculate the yield. The yield was calculated based on the mass of lignin added to the reaction system ( Figure 8 is the adhesive yield, and the yield is the mass ratio of the separated lignin adhesive after drying to the added sulfate lignin). The results are as follows Figure 8 and as shown in Table 9.

[0171] Table 9 Adhesive yield of lignin formaldehyde-free adhesives prepared in Examples 19-26.

[0172]

[0173]

[0174] Depend on Figure 8 As shown in Table 9, the yield of sulfate-based lignin formaldehyde-free adhesive increased from 150.3% to 430.0% and from 181.8% to 456.9% with the increase of maleic acid dosage and pretreatment temperature, respectively, indicating that the increase of maleic acid dosage and the increase of temperature during pretreatment can significantly increase the cross-linking reaction between DES solvent and sulfate lignin, thereby improving the yield of lignin adhesive.

[0175] Embodiment 27

[0176] The lignin formaldehyde-free adhesive prepared in Examples 19-26 was used to bond three layers of plywood, and the specific bonding process was the same as in Example 18. The molded plywood was cut into standard test pieces and then tested for dry strength and Class II wet strength using a universal tensile testing machine (SUNS UTM6503) at a tensile speed of 5 mm / min and a 5 kN force sensor. The results are shown in Fig. 9 As shown in Table 10.

[0177] Table 10 Bonding strength of three-layer plywood bonded with lignin formaldehyde-free adhesives prepared in Examples 19-26.

[0178] Bond dry strength MPa Bond wet strength MPa Embodiment 19 1.56 1.35 Embodiment 20 1.23 1.0 Embodiment 21 0.99 0.90 Embodiment 22 1.0 0.93 Embodiment 23 1.44 1.28 Embodiment 24 1.11 1.04 Embodiment 25 1.02 0.88 Embodiment 26 0.89 0.88

[0179] Depend on Fig. 9 As shown in Table 10, the differences between the lignin glues prepared under different molar ratios are large. When the amount of maleic acid is small, the adhesive has a better bonding effect on poplar veneer, and the dry and wet strength can reach 1.23 / 1.0MPa (L 1:2:1, i.e. Example 20) and 1.56 / 1.35MPa(L 1:1:1 , i.e. Example 19), with the increase of maleic acid dosage, the bonding strength decreased to 0.99 / 0.90MPa (L 1:1:2 , i.e. Example 21) and 1.0 / 0.93MPa(L 1:0.5:1 , i.e., Example 22). The results of the effect of increasing the amount of maleic acid on the bonding strength of the adhesive are similar. After increasing the pretreatment temperature, the dry and wet strengths of the adhesive decrease from 1.56 / 1.35MPa to 0.99 / 0.9MPa, respectively, but are still higher than the minimum standard of 0.7MPa. More stringent pretreatment conditions correspond to a higher yield of lignin formaldehyde-free adhesives, but the bonding strength of lignin formaldehyde-free adhesives decreases accordingly. The present invention can provide technical and theoretical guidance for the production of lignin formaldehyde-free adhesives with different bonding strengths through condition optimization.

[0180] Comparative Example 1

[0181] 1) choline chloride / 1,4-butanediol / citric acid, choline chloride / 1,4-butanediol / malic acid, choline chloride / 1,3-propylene glycol / maleic acid, and choline chloride / ethylene glycol / maleic acid were mixed in a molar ratio of 1:1:1, heated at 80° C., and stirred continuously until a uniform, clear liquid was formed to obtain a deep eutectic solvent;

[0182] 2) mixing bamboo powder with the low eutectic solvent obtained in step 1) at a mass ratio of 1:10, reacting at 110° C. for 6 hours, adding 5 times the volume of the mixed solution of ethanol aqueous solution after the pretreatment, wherein the volume concentration of the ethanol aqueous solution is 50%, stirring for 1 hour; solid-liquid separation, obtaining a pretreated liquid and a pretreated material rich in lignin;

[0183] 3) After the pretreated material is washed with distilled water until it is neutral, the content of its main components is analyzed and the lignin removal rate is calculated; the pretreated liquid rich in lignin is rotary evaporated at 60° C. to remove the ethanol therein, and appropriate deionized water is added to precipitate the lignin, and the pretreated liquid after the ethanol is removed is centrifuged to obtain lignin.

[0184] Although systems such as choline chloride / 1,4-butanediol / citric acid and choline chloride / 1,4-butanediol / oxalic acid can remove lignin from bamboo, the removed lignin is mainly in the form of powder, and it is impossible to obtain lignin glue similar to the liquid fluid obtained in the present invention.

[0185] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for bonding high-strength plywood with low sizing amount based on lignin formaldehyde-free adhesive, characterized in that: Use lignin-based formaldehyde-free adhesive to bond veneers, with the amount of adhesive applied on one side not exceeding 80g / m 2 After hot pressing and curing, a high-strength plywood with a bonding strength of not less than 0.7MPa is obtained; the lignin-based formaldehyde-free adhesive is obtained by separating and treating wood fiber raw materials or sulfate lignin with a mixed solution; wherein the mixed solution is composed of choline chloride, long-chain diols and maleic acid.

2. The bonding method of high-strength plywood with low glue application amount based on lignin formaldehyde-free adhesive according to claim 1, characterized in that: The single board is made of poplar wood.

3. The bonding method of high-strength plywood with low glue application amount based on lignin formaldehyde-free adhesive according to claim 1, characterized in that: The hot pressing temperature is 150-190° C., the pressure is 1 MPa, and the hot pressing time is 1.1-4.4 min / mm.

4. The bonding method of high-strength plywood with low glue application amount based on lignin formaldehyde-free adhesive according to claim 1, characterized in that: The preparation process of the lignin formaldehyde-free adhesive is as follows: 1) mixing choline chloride, long-chain diol and maleic acid in a molar ratio of 1:0.5-2:1-2, and heating at 90° C. until a uniform and transparent DES solution is formed; 2) mixing the wood fiber raw material or kraft lignin with the DES solution obtained in step 1) at a mass ratio of 1:10, reacting at 100-140° C. for 6-12 hours, adding a solvent 3-5 times the volume of the mixed solution after the reaction, stirring and solid-liquid separation, rotary evaporating the obtained solution to remove the solvent, washing with water, and drying to obtain a lignin formaldehyde-free adhesive.

5. The bonding method of high-strength plywood with low glue application amount based on lignin formaldehyde-free adhesive according to claim 1, characterized in that: The specific steps include: 1) Preparation of lignin formaldehyde-free adhesive Mix choline chloride, long-chain diol and maleic acid in a molar ratio of 1:0.5-2:1-2, and heat at 90° C. until a uniform and transparent DES solution is formed; The lignocellulosic raw material or kraft lignin is mixed with the prepared DES solution in a mass ratio of 1:10, and reacted at 100-140° C. for 6-12 hours. After the reaction is completed, a solvent 3-5 times the volume of the mixed solution is added for stirring and solid-liquid separation, and the obtained solution is subjected to rotary evaporation to remove the solvent, and the lignin formaldehyde-free adhesive is obtained after washing with water and drying; 2) Preparation of high-strength plywood The lignin formaldehyde-free adhesive prepared in step 1) is directly and evenly applied on the surface of the veneer or evenly applied on the surface of the veneer after heating, and the amount of adhesive applied on one side is 50-75g / m 2 The fiber directions of adjacent veneers are perpendicular to each other, and the veneers are assembled and hot-pressed for curing. The hot-pressing temperature is 150-190°C, the pressure is 1.0MPa, and the hot-pressing time is 1.1-4.4min / mm to obtain high-strength plywood.

6. The bonding method of high-strength plywood with low glue application amount based on lignin formaldehyde-free adhesive according to claim 5, characterized in that: The specific steps include: 1) Preparation of lignin formaldehyde-free adhesive Choline chloride, 1,4-butanediol and maleic acid were mixed in a molar ratio of 1:2:1, heated at 90°C with constant stirring until a uniform, transparent DES solution was formed; The kraft lignin and the prepared DES solution were mixed in a mass ratio of 1:10, and reacted at 110°C for 12 hours. After the reaction, hot water 3 times the volume of the mixed solution was added, and the mixture was stirred and then solid-liquid separated. The obtained lignin-rich pretreatment liquid was rotary evaporated, washed with water, and dried to obtain a lignin formaldehyde-free adhesive. 2) Preparation of high-strength plywood The lignin formaldehyde-free adhesive prepared in step 1) is evenly applied on the surface of the veneer, with a single-sided adhesive amount of 50 g / m 2 The fiber directions of adjacent veneers are perpendicular to each other to assemble the veneers to obtain a three-layer plywood blank, which is then hot-pressed and solidified at a temperature of 180°C, a pressure of 1.0 MPa, and a hot-pressing time of 2.2 min / mm to obtain a high-strength plywood.

7. The bonding method of high-strength plywood with low glue application amount based on lignin formaldehyde-free adhesive according to claim 5, characterized in that: The specific steps include: 1) Preparation of lignin formaldehyde-free adhesive Choline chloride, 1,4-butanediol and maleic acid were mixed in a molar ratio of 1:2:1, heated at 90°C with constant stirring until a uniform, transparent DES solution was formed; The bamboo powder and the prepared DES solution were mixed in a mass ratio of 1:10, and reacted at 110°C for 6 hours. After the reaction, an ethanol aqueous solution with a volume of 5 times that of the mixed solution was added, and the mixture was stirred and then solid-liquid separated. The obtained lignin-rich pretreatment liquid was rotary evaporated, washed with water, and dried to obtain a lignin formaldehyde-free adhesive. 2) Preparation of high-strength plywood The lignin formaldehyde-free adhesive prepared in step 1) is evenly applied on the surface of the veneer, with a single-sided adhesive amount of 50 g / m 2 The fiber directions of adjacent veneers are perpendicular to each other to assemble the veneers to obtain a three-layer plywood blank, which is then hot-pressed and solidified at a temperature of 180°C, a pressure of 1.0 MPa, and a hot-pressing time of 2.2 min / mm to obtain a high-strength plywood.

8. The bonding method of high-strength plywood with low glue application amount based on lignin formaldehyde-free adhesive according to claim 5, characterized in that: The specific steps include: 1) Preparation of lignin formaldehyde-free adhesive Choline chloride, 1,4-butanediol and maleic acid were mixed in a molar ratio of 1:1:1, heated at 90°C with constant stirring until a uniform, transparent DES solution was formed; The kraft lignin and the prepared DES solution were mixed in a mass ratio of 1:10, and reacted at 100°C for 12 hours. After the reaction, hot water 3 times the volume of the mixed solution was added, and the mixture was stirred to separate the solid and liquid. The obtained lignin-rich pretreatment liquid was rotary evaporated, washed with water, and dried to obtain a lignin formaldehyde-free adhesive. 2) Preparation of high-strength plywood The lignin formaldehyde-free adhesive prepared in step 1) is evenly applied on the surface of the veneer, with a single-sided adhesive amount of 50 g / m 2 The fiber directions of adjacent veneers are perpendicular to each other to assemble the veneers to obtain a three-layer plywood blank, which is then hot-pressed and solidified at a temperature of 180°C, a pressure of 1.0 MPa, and a hot-pressing time of 2.2 min / mm to obtain a high-strength plywood.

9. The bonding method of high-strength plywood with low glue application amount based on lignin formaldehyde-free adhesive according to claim 5, characterized in that: The specific steps include: 1) Preparation of lignin formaldehyde-free adhesive Choline chloride, 1,4-butanediol and maleic acid were mixed in a molar ratio of 1:1:1, heated at 90°C with constant stirring until a uniform, transparent DES solution was formed; The bamboo powder and the prepared DES solution were mixed in a mass ratio of 1:10, and reacted at 100°C for 6 hours. After the reaction, an ethanol aqueous solution with a volume of 5 times that of the mixed solution was added, and the mixture was stirred for solid-liquid separation. The obtained lignin-rich pretreatment liquid was rotary evaporated, washed with water, and dried to obtain a lignin formaldehyde-free adhesive. 2) Preparation of high-strength plywood The lignin formaldehyde-free adhesive prepared in step 1) is evenly applied to the surface of the veneer, with a single-sided adhesive amount of 50 g / m 2 The fiber directions of adjacent veneers are perpendicular to each other to form veneers, and three-layer plywood is obtained. The veneers are then hot-pressed and solidified at a temperature of 180°C, a pressure of 1.0 MPa, and a hot-pressing time of 2.2 min / mm to obtain a high-strength plywood.

10. The bonding method of high-strength plywood with low glue application amount based on lignin formaldehyde-free adhesive according to claim 5, characterized in that: The specific steps include: 1) Preparation of lignin formaldehyde-free adhesive Choline chloride, 1,4-butanediol and maleic acid were mixed in a molar ratio of 1:1:1, heated at 90°C with constant stirring until a uniform, transparent DES solution was formed; The kraft lignin and the prepared DES solution were mixed in a mass ratio of 1:10, and reacted at 110°C for 12 hours. After the reaction, hot water 3 times the volume of the mixed solution was added thereto, and the mixture was stirred and then solid-liquid separated. The obtained lignin-rich pretreatment liquid was rotary evaporated, washed with water, and dried to obtain a lignin formaldehyde-free adhesive. 2) Preparation of high-strength plywood The lignin formaldehyde-free adhesive prepared in step 1) is evenly applied to the surface of the veneer, with a single-sided adhesive amount of 50g / m 2 The fiber directions of adjacent veneers are perpendicular to each other to form veneers, and three-layer plywood is obtained. The veneers are then hot-pressed and solidified at a temperature of 180°C, a pressure of 1.0 MPa, and a hot-pressing time of 2.2 min / mm to obtain a high-strength plywood.

Citation Information

Patent Citations

  • Method for preparing lignin adhesive and product thereof

    CN115029104A

  • Lignin-based adhesive

    CN115558466A

  • Phenolic resin adhesive with low free formaldehyde content and preparation method thereof

    CN116640543A

  • Preparation method of micro-nano lignin with adhesive property

    CN118064107A

  • Full-bio-based adhesive as well as preparation method and application thereof

    CN118085817A

Cited By

  • Green, low-cost and high-performance lignin adhesive as well as preparation method and application thereof

    CN120290136A

  • A green, low-cost, high-performance lignin adhesive and a preparation method and application thereof

    CN120290136B